Were Elections in the Socialist Countries Elections at All? The Case of Elections to the Sejm in Communist-Ruled Poland - Siedziako, Michał (Kwartalnik Historyczny, 2022)
The article presents the current state of research into parliamentary elections in Poland during the period of communist rule. The author outlines the development of the electoral system of the Polish People’s Republic in the 1940s and 50s, and also analyses its singular features in the years when elections to the Sejm were fully controlled by the ruling Polish United Workers’ Party. The final part of the paper is devoted to elections in the 1980s, when this electoral model collapsed, thereby contributing to the disintegration of the communist dictatorship in Poland.